"How am I going, coach?" - The effect of augmented feedback during small-sided games on locomotor, physiological, and perceptual responses - Weakley, J. J. S.; Read, D. B.; Fullagar, H. H. K.; Ramirez-Lopez, C.; Jones, B.; Cummins, C.; Sampson, J. A. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To investigate whether providing global positioning system feedback to players between bouts of small-sided games (SSGs) can alter locomotor, physiological, and perceptual responses. Methods: Using a reverse counterbalanced design, 20 male university rugby players received either feedback or no feedback during "off-side" touch rugby SSGs. Eight 5v5, 6×4-minute SSGs were played over 4 d. Teams were assigned to a feedback or no-feedback condition (control) each day, with feedback provided during the 2-min between-bouts rest interval. Locomotor, heart rate, and differential rating of perceived exertion of breathlessness and leg-muscle exertion were measured and analyzed using a linear mixed model. Outcomes were reported using effect sizes (ES) and 90% confidence intervals (CI), and then interpreted via magnitude-based decisions. Results: Very likely trivial to unclear differences at all time points were observed in heart rate and differential rating of perceived exertion measures. Possibly to very likely trivial effects were observed between conditions, including total distance (ES=0.15; 90 CI, -0.03 to 0.34), high-speed distance (ES=-0.07; 90 CI, -0.27 to 0.13), and maximal sprint speed (ES=0.11; 90% CI, -0.11 to 0.34). All within-bout comparisons showed very likely to unclear differences, apart from possible increases in low-speed distance in bout 2 (ES=0.23; 90% CI, 0.01 to 0.46) and maximal sprint speed in bout 4 (ES=0.21; 90% CI, -0.04 to 0.45). Conclusions: In this study, verbal feedback did not alter locomotor, physiological, or perceptual responses in rugby players during SSGs. This may be due to contextual factors (eg, opposition) or the type (ie, distance) or low frequency of feedback provided.